2005
DOI: 10.1097/01.shk.0000144423.40270.96
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Enhanced Tumor Necrosis Factor-?? Production From Kupffer Cells by Gadolinium Chloride on Liver Injury/Mortality in Endotoxemia of Normal and Partially Hepatectomized Mice

Abstract: Gadolinium chloride (GdCl3) reportedly inhibits Kupffer cell function including TNF-alpha production and thereby improves organ dysfunctions after LPS challenge, particularly in partially hepatectomized (PH) mice. In addition, TNF-alpha reportedly promotes the regeneration of hepatocytes after PH. However, we have frequently seen GdCl3 treatment increase the mortality of normal mice after LPS injection. Therefore, we investigated this controversial issue in the present study. The mice treated by GdCl3 (10 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
1
28
2
Order By: Relevance
“…Furthermore, Kono et al (2002) have reported that although gadolinium administration prevented LPS-induced increase in TNF-gene expression in the liver, it did not modify the serum concentrations of TNF-. However, it has recently been reported that gadolinium treatment decreased superoxide generation, but conversely increased Kupffer cell TNF-production after LPS stimulation (Kinoshita et al 2005). These data indicate that gadolinium treatment decreases phagocytosis and superoxide production in Kupffer cells, whereas its effect on TNFand cytokine release is less clear.…”
Section: Discussioncontrasting
confidence: 47%
“…Furthermore, Kono et al (2002) have reported that although gadolinium administration prevented LPS-induced increase in TNF-gene expression in the liver, it did not modify the serum concentrations of TNF-. However, it has recently been reported that gadolinium treatment decreased superoxide generation, but conversely increased Kupffer cell TNF-production after LPS stimulation (Kinoshita et al 2005). These data indicate that gadolinium treatment decreases phagocytosis and superoxide production in Kupffer cells, whereas its effect on TNFand cytokine release is less clear.…”
Section: Discussioncontrasting
confidence: 47%
“…The superoxide production from Kupffer cells was determined by MCLA-dependent chemiluminescence using the method of Nakano [16,19,20]. A glass cuvette containing isolated Kupffer cells (1 × 10 5 ) and MCLA (2 µM) in 2.0 ml of HBSS was placed in a luminescence reader (BLR-101, Aloka, Tokyo) and the emission of chemiluminescence was recorded.…”
Section: Determination Of the Superoxide Production From Kupffer Cellmentioning
confidence: 99%
“…The isolation of neutrophils was performed by the method described by Rosen and Klebanoff [16,18]. Briefly, a blood sample was drawn into a heparinized syringe (20 units/ ml of heparin) from the abdominal aorta following a laparotomy under lethal ether anesthesia.…”
Section: Isolation Of Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations